Achilles Tendon Repair- A Systematic Review of Overlapping Meta-Analyses. Issue 3 (11th September 2017) - Hurley, Eoghan; Yasui, Youichi; Gianakos, Arianna; Seow, Dexter; Kromka, Joseph; Shimozono, Yoshiharu; Megill, Robin; Kennedy, John
Category: Sports Introduction/Purpose: Acute Achilles tendon ruptures (ATR) are a common sports-related injury with an incidence of between 8-37 per 100, 000 per year. While there are several meta-analyses published on the optimal treatment of ATR based on randomized control trials, the reported outcomes conflict between each meta-analysis due to different methodologies. The aim of this study is to systematically review the clinical results represented in meta-analyses in the current literature on acute ATR. Methods: Two independent reviewers performed the literature search based on the PRISMA guidelines to identify meta-analyses on Achilles tendon repair. Clinical results, including the re-rupture rates, wound infection rates and overall complication rates were analyzed. Level of evidence (LOE) and methodological quality of evidence (MQOE), using the AMSTAR score, were evaluated. A statistically significant difference (SSD) was defined as p < 0.05. Each meta-analysis was categorized into one of the following subgroupings: 1) Operative vs Non-Operative Treatment (with Conservative Rehabilitation) [OC vs NOC], 2) Operative vs Non-Operative Treatment (with Functional Rehabilitation) [OF vs NOF], 3) Conservative Rehabilitation vs Functional Rehabilitation (with Operative Treatment) [OC vs OF], and 4) Open vs. Percutaneous Repair (with Conservative Rehabilitation) [OC vs POC]. Results: Four studies compared OC and NOC. Re-rupture rates ranged from 3.1-6.4% in OC and 10.0-13.0% in NOC. Two of these studies showed statistical significance in favour of OC. There was no SSD was seen in other complications. Three studies compared OF and NOF. Re-rupture rates ranged from 3.8-5.0% in OF and 6.0-11.9% in NOF, no study showed a SSD. There was no SSD in other complications. Three studies compared OF and OC. Re-rupture rates ranged from 2.13-3% in OF and 1.1-2.1% in OC, no study showed a SSD. Four studies compared OC and PSC. Re-rupture rates ranged from 2.2-4.4% in OC and 1.1-2.1% in PSC, no study showed a SSD. In all included studies there was SSD in wound infection rates, in favour of PSC. Conclusion: Overall there exists a large volume of high quality meta-analyses on Achilles tendon repair. The re-rupture rates were lower in operative treatment in all studies, even when early functional rehabilitation was used. However, while early functional rehabilitation may allow early mobility but the rehabilitation method can be demanding. Although there was no difference between percutaneous and open repair on the re-rupture rate, there was an overall reduction in wound infection after percutaneous repair. The results within this study can help determine the optimal treatment for patients.